Are consumers' quality perceptions influenced by brand familiarity, brand exposure and brand knowledge? Results from a wine tasting experiment - D. Priilaid; G. Human; K. Pitcher; T. Smith; C. Varkel (South African Journal of Business Management, 2017)
Theory posits that, over time, placebo-type brand-equity effects may develop through the process of wine purchase and consumption. This being so, the extent to which factors like brand familiarity, brand exposure and brand knowledge combine to inform and reinforce such brand-equity effects remains still largely unexplored. With the aim of modelling this potentially mediating dynamic, we present a two-stage wine tasting experiment employing the combined reportage of fourteen experimental groups, each consecutively tasting seven Sauvignon Blanc wines first blind, and then, afterwards, sighted. Results demonstrate how brand familiarity mediates the effect of brand exposure on the sighted assessment of wine both directly, and via its relation to brand knowledge. This novel finding extends the literature on the consumer response to brand information, suggesting that conventional mass media marketing strategies aimed merely at imparting brand knowledge may prove insufficient unless they also create a degree of brand familiarity in the minds of their customers.
Keywords: 650